2021
DOI: 10.1002/ps.6513
|View full text |Cite
|
Sign up to set email alerts
|

Seed priming with calcium chloride enhances wheat resistance against wheat aphid Schizaphis graminumRondani

Abstract: BACKGROUND Calcium is an essential macronutrient for plant growth. Although it has been shown that exogenous Ca application can increase plant resistance to abiotic stress, little is known about its potential to enhance plant tolerance to biotic stress. Here, we investigated whether pretreatment of wheat (Triticum aestivum L.) seeds with calcium chloride (CaCl2) improves plant resistance against wheat aphid (Schizaphis graminum Rondani). The developmental time, population size, feeding behavior of aphids on pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 98 publications
(119 reference statements)
1
7
0
Order By: Relevance
“…PR1 is a crucial regulator of systemic acquired resistance (SAR) and may serve as a marker for early plant defense responses, and its importance in plant immunity has been recognized for over two decades. , The accumulation of PR1 , a SA marker gene, is linked to the activation of SA in response to pathogens . Our results are consistent with previous findings of many studies, indicating that increased PR1 expression enhances resistance against pathogen infections. Several reports have confirmed that PR2 proteins are engaged in various physiological plant defense processes primarily induced by SAR inducers like SA. Increased PR2 activity in plant cell wall has been shown to enhance the accumulation of oligosaccharides produced, which elicits plant defense.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…PR1 is a crucial regulator of systemic acquired resistance (SAR) and may serve as a marker for early plant defense responses, and its importance in plant immunity has been recognized for over two decades. , The accumulation of PR1 , a SA marker gene, is linked to the activation of SA in response to pathogens . Our results are consistent with previous findings of many studies, indicating that increased PR1 expression enhances resistance against pathogen infections. Several reports have confirmed that PR2 proteins are engaged in various physiological plant defense processes primarily induced by SAR inducers like SA. Increased PR2 activity in plant cell wall has been shown to enhance the accumulation of oligosaccharides produced, which elicits plant defense.…”
Section: Discussionsupporting
confidence: 90%
“…The phenotypes of the plants were recorded when the control plants had full Pst sporulating, about 14 days post-Pst inoculation (dpi). DNA was extracted from 4 cm segments of MX169 leaves collected at 6,12,18,24,36,48,72,96, and 120 h post-treatment (hpt) with flubeneteram. The total DNA obtained at the different time points were quantified through quantitative real-time PCR (qRT-PCR).…”
Section: Determination Of the Control Efficacy Of Flubeneteram Onmentioning
confidence: 99%
“…The calcium seed priming improves wheat's resistance to the destructive aphid because Ca2 + signals are necessary for the activation of plant immune responses. The callose deposition (a naturally occurring permeable barrier and a leak-seal in plant tissues damaged by herbivores), Wang et al, (2021) found that the Ca2 + increased resistance is strongly related to callose deposition. Ca given as a foliar spray may cause reduction in incidence in artichoke plants in addition to an increase in vegetative characteristics; transmission of Ca signals stimulates JA, salicylic acid, ethylene, and other signal transduction pathways, which then triggers plant defense mechanisms (Du et al, 2009).…”
Section: Effect Of Treatments On Aphid Controlmentioning
confidence: 99%
“…(Mengel and Kirkby 2001;Reyes et al, 2013). Moreover, it is one of the earliest signaling elements associated with plant stress responses, particularly during pest autoimmune Matthus et al, (2019) and promoting the mechanical properties of plant tissues as well as improving plant defense responses (Thor, 2019 andWang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Aphids are significant economic pests on cultivated plants in agriculture worldwide [ 5 ]. They are piercing–sucking pests of several cereal crops that cause severe damage through sucking nutrients, deposition of honeydew, and transmission of viral disease [ 6 ]. Because of the severity of drought stress, the English grain aphid, Sitobion avenae Fabricius (Hemiptera: Aphididae), is a cosmopolitan economic pest that threatens wheat production in Northwestern China [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%